ANALISIS KELAYAKAN INVESTASI PENGGEMUKAN SAPI POTONG (KASUS: PT CATUR MITRA TARUMA, KABUPATEN BOGOR) - Nisa, Chairun; Winandi, Ratna; Tinaprilla, Netti (Forum Agribisnis, 2014)
A gap between national beef consumption and beef production becomes an opportunity for beef cattle fattening business. The purpose of this research is to analyze the feasibility of beef cattle fattening. The research was conducted at the main office of PT Catur Mitra Taruma at South Jakarta and its feedlot stall at Desa Cariu, Kabupaten Bogor. Aqualitative analysis method was used to analyze the non-financial feasibility, that covered market aspects, technical aspects, management and law aspects, and also social, economic, and environmental aspects. The financial feasibility was analyzed quantitatively byÂ investment criteria and switching value analysis. The result shows that beef cattle fattening in PT Catur Mitra Taruma is feasibleand it is more sensitive to the decreasing sales of beef cattle than to the increasing price of feed.